Employee Engagement: Reconciling the academic and practitioner and the impact of office engagement - Coates, Harry (2017)
Employee engagement is one of the hot topics of the business world, both for managers and academics. However, currently there exists a schism between the academics who wish to study the nature of engagement and those who wish to provide business managers with suggestions and solutions for increasing employee engagement, and thus benefitting from the resulting improvement in business performance, who will be termed as practitioners in this study. Whilst the current research has been dominated by empirical research, this will be a qualitative analysis utilising semi-structured interviews that will examine engagement and the importance of office-design and environment. Three managers of a Top 100 legal firm in Greater London were interviewed, as well as fourteen junior employees from a variety of firms across different industries in the third sector. These interviews were then thematically analysed before being combined with current theories identified in the secondary literature review. The results of the interviews, provided a wealth of data which showed, the importance of engagement, and shed interesting light on its nature, leading to the more general definition of engagement proffered by this work. Simultaneously, it also highlighted the importance that both managers and employees place on work-place design and office environment to fostering levels of engagement. It is argued that office-design should be considered a key antecedent to engagement. The research also highlighted several areas for further research in the future.